Demographic, health, and behaviors profile of Saudi Arabia’s aging population 2022–2023 - Bindhim, Nasser F.; Senitan, Mohammed; Almutairi, Madhawi N.; Alhadlaq, Leen S.; Alnajem, Sundus A.; Alfaifi, Maryam Ali; Althumiri, Nora A. (Frontiers in Aging, 2025)
BackgroundThe population aged 60 years and older in Saudi Arabia is rapidly increasing, leading to concerns regarding their health, socioeconomic status, and lifestyle behaviors. Aging is associated with a higher risk of chronic diseases, multimorbidity, and mental health issues, which can significantly affect the quality of life. However, national data on older people in Saudi Arabia remain limited.AimThis study aims to profile older people in Saudi Arabia during the years 2022–2023, focusing on their demographic characteristics, socioeconomic status, health conditions, and lifestyle behaviors.MethodsData were drawn from the Sharik Health Indicators Surveillance System (SHISS) 2022–2023, a nationwide cross-sectional survey conducted through phone interviews. The final analysis included 2,702 participants aged 60 years and older. Descriptive statistics were employed to summarize demographic, health, and behavioral data.ResultsThe study revealed that over half (52%) of the participants had two or more chronic conditions, with hypertension, hypercholesterolemia, and type 2 diabetes being the most common. Mental health assessments indicated that 17.7% of older people were at risk of depression, and another 17.7% were at risk of anxiety. Additionally, the study found low adherence to healthy behaviors, with only 11.1% meeting the recommended fruit and vegetable intake and 20.1% engaging in sufficient physical activity. Furthermore, 67% of older people were classified as overweight or obese.ConclusionOlder people in Saudi Arabia face significant health challenges, including high rates of multimorbidity, mental health risks, and poor lifestyle behaviors. These findings highlight the urgent need for targeted health interventions and educational programs tailored to older people, aiming to improve their quality of life and contribute to the national goals outlined in Saudi Arabia’s Vision 2030.